2005
DOI: 10.1143/jpsj.74.2294
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of the Spin State Transition of (Pr1-ySmy)1-xCaxCoO3

Abstract: Transport, thermal and magnetic measurements have been carried out on (Pr1-ySmy)1-xCaxCoO3. The system exhibits a structural phase transition accompanied by the spin state change from the intermediate spin (IS) state to the low spin (LS) state with decreasing temperature T. We have constructed a T-y phase diagram for x=0.3 and T-x ones for y=0.2 and 0.3. By analyzing their magnetic susceptibilities, the number of Co ions excited to IS state (or the electron number in the eg orbitals), nIS, are roughly estimate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 37 publications
11
73
0
Order By: Relevance
“…In this situation, the partial substitution of R 3+ by a smaller R ′3+ in (R 1−y R ′ y ) 1−x A x CoO 3 systematically increases the chemical pressure, which should enhance the crystal field splitting and therefore stabilize the low-spin state. 17,34 Thus, small changes in the lattice characteristics may critically determine the physical properties of cobaltites.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation, the partial substitution of R 3+ by a smaller R ′3+ in (R 1−y R ′ y ) 1−x A x CoO 3 systematically increases the chemical pressure, which should enhance the crystal field splitting and therefore stabilize the low-spin state. 17,34 Thus, small changes in the lattice characteristics may critically determine the physical properties of cobaltites.…”
Section: +mentioning
confidence: 99%
“…However, the data obtained for samples of Pr 0.7 Sr 0.3 CoO 3 [41] and La 0.7 Sr 0.3 CoO 3 [5,42] prepared under normal oxygen pressure show that the expected oxygen deficiency should be about 0.02 − 0.04. The comparison of the transition temperatures for closely related (PrSm) 0.7 Ca 0.3 CoO 3 samples annealed under oxygen pressure of 1 bar [36] and of 60 bar [20,34] suggests that the presumed oxygen deficiency hardly affects the physical properties.…”
Section: +mentioning
confidence: 99%
“…Similar metal-insulator (MI) transition was evidenced also in the less doped Pr 1−x Ca x CoO 3 (x=0.3) under higher hydrostatic pressures and in the (Pr 1−x RE y ) 1−x Ca x CoO 3 system (0.2<x<0.5) with a partial substitution of Pr by smaller RE cations such as Sm, Eu, and Y under ambient pressure. [7][8][9] This peculiar transition appeared to be conditioned not only by the presence of both Pr and Ca ions, but also by a larger structural distortion of the CoO 6 network, depending on the average ionic radius and size mismatch of perovskite A-site ions. 9 Furthermore, the critical temperature T MI was found a corresponding author fujishiro@iwate-u.ac.jp 2158-3226/2016/6(2)/025318/9 6, 025318-1 © Author(s) 2016.…”
Section: Introductionmentioning
confidence: 98%
“…15 It must be emphasized that the VSST was systematically found to develop in the paramagnetic regime; indications of strong ferromagnetic correlations and possible short-range ordering (likely related to Co 4+ ) were only reported at much lower temperatures (typically at T  5 K). 1,3,8 4 Magnetization measurements were carried out with a superconducting quantum interference device magnetometer (MPMS, Quantum Design). Isothermal magnetization curves at selected temperatures demonstrated that the magnetization (M) varies linearly with the magnetic field (H) for temperature higher than  20 K. Accordingly, an isofield magnetization curve was measured in a field of 1 T and the dc susceptibility  (T > 20 K) was derived from the ratio M/H.…”
Section: G G E Tmentioning
confidence: 99%
“…1,[3][4][5]7,8,13 In a recent x-ray absorption spectroscopy (XAS) study on Pr 0.5 Ca 0.5 CoO 3 , however , Herrero et al showed that the spin state of Co 3+ above T* can be equally well described by an inhomogeneous mixture between low-spin and high-spin (HS, 2 …”
Section: Introductionmentioning
confidence: 99%